Fine-scale diversity patterns in belowground microbial communities are consistent across kingdoms. Issue 6 (2nd May 2019) - Aas, Anders Bjørnsgaard; Andrew, Carrie J; Blaalid, Rakel; Vik, Unni; Kauserud, Håvard; Davey, Marie L
ABSTRACT: The belowground environment is heterogeneous and complex at fine spatial scales. Physical structures, biotic components and abiotic conditions create a patchwork mosaic of potential niches for microbes. Questions remain about mechanisms and patterns of community assembly belowground, including: Do fungal and bacterial communities assemble differently? How do microbes reach the roots of host plants? Within a 4 m 2 plot in alpine vegetation, high throughput sequencing of the 16S (bacteria) and ITS1 (fungal) ribosomal RNA genes was used to characterise microbial community composition in roots and adjacent soil of a viviparous host plant ( Bistorta vivipara ). At fine spatial scales, beta-diversity patterns in belowground bacterial and fungal communities were consistent, although compositional change was greater in bacteria than fungi. Spatial structure and distance-decay relationships were also similar for bacteria and fungi, with significant spatial structure detected at <50 cm among root- but not soil-associated microbes. Recruitment of root microbes from the soil community appeared limited at this sampling and sequencing depth. Possible explanations for this include recruitment from low-abundance populations of soil microbes, active recruitment from neighbouring plants and/or vertical transmission of symbionts to new clones, suggesting varied methods of microbial community assembly for viviparous plants. Our results suggest that even at relatively small spatial scales, deterministic processes play a significant role in belowground microbial community structure and assembly. Abstract : Agreeing underground. Bacteria and fungi have similar diversity patterns in roots and soils, even though roots recruit microbes from both soils and other plants